2023
DOI: 10.3389/fpsyt.2023.1143175
|View full text |Cite
|
Sign up to set email alerts
|

Virtually screening adults for depression, anxiety, and suicide risk using machine learning and language from an open-ended interview

Abstract: BackgroundCurrent depression, anxiety, and suicide screening techniques rely on retrospective patient reported symptoms to standardized scales. A qualitative approach to screening combined with the innovation of natural language processing (NLP) and machine learning (ML) methods have shown promise to enhance person-centeredness while detecting depression, anxiety, and suicide risk from in-the-moment patient language derived from an open-ended brief interview.ObjectiveTo evaluate the performance of NLP/ML model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Previous research related to this work has found a semistructured, in-person interview promising for the collection of SFT features to be used with ML models for the identification of suicide risk (Pestian et al, 2010(Pestian et al, , 2016(Pestian et al, , 2017Laksana et al, 2017;Cohen et al, 2020Cohen et al, , 2022Wright-Berryman et al, 2023). In these studies, trained staff (therapists, clinical research coordinators, or licensed behavioral health clinicians) recorded a semi-structured interview with hundreds of suicidal or non-suicidal participants in emergency departments, psychiatric units, and in-school therapy settings with adolescents and adults.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research related to this work has found a semistructured, in-person interview promising for the collection of SFT features to be used with ML models for the identification of suicide risk (Pestian et al, 2010(Pestian et al, , 2016(Pestian et al, , 2017Laksana et al, 2017;Cohen et al, 2020Cohen et al, , 2022Wright-Berryman et al, 2023). In these studies, trained staff (therapists, clinical research coordinators, or licensed behavioral health clinicians) recorded a semi-structured interview with hundreds of suicidal or non-suicidal participants in emergency departments, psychiatric units, and in-school therapy settings with adolescents and adults.…”
Section: Introductionmentioning
confidence: 99%